Ideas: Critical Realism of Moral-Material Complementarities - Rodney Shakespeare (Journal of Critical Realism in Socio-Economics (JOCRISE), 2023)
This section of JOCRISE is devoted to briefly ventilate innovative ideas on diverse perspectives of socio-scientiᢚc theories in general and developing economies particularly, for the common wellbeing of global holism. Writers may contribute ideas in this space for readers to gain theoretical, academic, and institutional insights